Interface direct shear test data for developing maximum peak and constant volume shear angle in dependency to the roughnesses of the surfaces - Alexander V Busch (PANGAEA, 2022)
The dataset contains the shear displacement data of more than 100 direct shear tests (constant normal load). Naturally corroded, 35 different steel surface have been sheared against a also natural quartz sand (Cuxhaven Sand). Mean center-line surface roughness of interfaces is provided.